Self-programming of information and its relationship to some offensive skills in volleyball among female students - Haneen Mohammed Hussein; Dr. Muna Talib Albadry (physical education and sport sciences college for women/ Baghdad University, 2021)
The researchers used the descriptive approach with the two methods of survey study and correlational relations, and the research community was identified with the students of the College of Physical Education and Sports Sciences at the University of Kufa, their number was (26) students, then a sample of (20) students was chosen, then after that the scale was selected and applied and the offensive skills tests in volleyball On the research sample, then the scientific foundations were extracted and the appropriate statistical treatments were used to reach the results, after which the results were presented, analyzed and discussed. As for the objectives of the research, they included in several points, namely: 1- Recognizing the degree of self-programming of information in volleyball among female students of the College of Physical Education and Sports Sciences at the University of Kufa. 2- To identify the degree of offensive skills in volleyball among female students of the College of Physical Education and Sports Sciences at the University of Kufa. 3- Knowing the relationship between the degree of self-programming of information and the degree of offensive skills in volleyball among female students of the College of Physical Education and Sports Sciences at the University of Kufa. As for imposing research, it includes: 1- There is a correlation between self-programming of information and offensive skills in volleyball among female students of the College of Physical Education and Sports Sciences at the University of Kufa.Areas of research include: 1-Human field: Female students of the fourth stage in the College of Physical Education and Sports Sciences - University of Kufa for the academic year 2020-2021. 2-Time range: for the period from 1/11/2020 to 29/11/2021. 3-Spatial field: Hall of the College of Physical Education and Sports Sciences - University of Kufa.